Urban Planning in Al-Madinah Al-Munawarah using New Green Spaces Modelling through GIS Application - Nadiyah Mazi Aljohani; Mokhtar Jaafar; Lam Kuok Choy (Indonesian Journal of Geography, 2021)
The present study investigated the new green spaces modelling in Al-Madinah Al-Munawarah using GIS application. It adopted the mental health theory as a theoretical framework. The data of the study was collected through two data collection instruments, namely, questionnaire as well as interview. The quantitative data was analysed through SPSS software while the qualitative data collected from the interviews was qualitatively analysed using thematic content analysis. The findings of the study revealed the most suitable model for potential new green spaces using GIS analysis (descriptive summaries) for urban planning in Al-Madinah Al-Munawarah is Quba (25.5%). Moreover, the most prominent challenge facing the design of a new green space in Al-Medinah Al-Munawarah, Saudi Arabia, is the weakness of the budget allocated to designing green spaces (86.7%). It is also shown that the most prominent benefits of designing new green spaces for the residents of Al-Madinah Al-Munawarah are the provision of seats and seating areas. Therefore, the participants stress the importance of taking into account the provision of seats and seating places when designing green spaces (93.3%). In terms of the potential of developing urban green spaces in Al-Madinah Al-Munawarah, the majority of the respondents believe that urban green spaces can be developed, to a large degree, in Al-Madinah Al-Munawarah in the future. Therefore, the study recommends that urban green spaces should be developed in Al-Madinah Al-Munawarah and the budget allocated to designing green spaces in Al-Madinah Al-Munawarah should be also increased. This study could be considered as a guideline for future development that can be used by government in Saudi Arabia.